2011
DOI: 10.5248/116.33
|View full text |Cite
|
Sign up to set email alerts
|

The genus Pythium in Taiwan (2) — an Illustrated diagnostic key

Abstract: A diagnostic key has been developed to facilitate the identification of 48 species of Pythium recorded in Taiwan so far. Photomicrographs are provided for the 10 most common or economically important species to highlight their major morphological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…To date, A. candida forms 24 physiological races that infect more than 200 plant species in 63 genera from the families Brassicaceae, Cleomaceae and Capparaceae, each specializing in different host species, of which at least 10 specialize in different Brassicaceae species [328][329][330][331][332][333][334][335][336][337][338][339]. Among the identified races, race 2 (Ac2VRR) causes severe annual yield losses in oil mustard (Brassica juncea [L.] Czern.…”
Section: Figure 153 -Signs Of Clubroot On Winter Oilseed Rape [100]mentioning
confidence: 99%
“…To date, A. candida forms 24 physiological races that infect more than 200 plant species in 63 genera from the families Brassicaceae, Cleomaceae and Capparaceae, each specializing in different host species, of which at least 10 specialize in different Brassicaceae species [328][329][330][331][332][333][334][335][336][337][338][339]. Among the identified races, race 2 (Ac2VRR) causes severe annual yield losses in oil mustard (Brassica juncea [L.] Czern.…”
Section: Figure 153 -Signs Of Clubroot On Winter Oilseed Rape [100]mentioning
confidence: 99%
“…Pustula parasitizes various asterids, in particular Asteraceae , and is characterised by usually densely reticulate oospores and sporangia with an equatorial wall thickening ( Thines & Spring, 2005 ; Choi, Thines, Tek, & Shin, 2012 ). Traditionally, it has been assumed that species causing white blister rust disease are specific mostly on the host family level ( Wilson, 1907 ; Biga, 1955 ; Choi & Priest, 1995 ). However, phylogenetic investigations have revealed that in Albugo , besides the generalist species, A. candida (Pers.)…”
mentioning
confidence: 99%
“…For specific countries, researchers can refer to keys of Robertson (1980) for species in New Zealand, AliShtayeh (1986) for species in Israel, Watanabe (2010) for species recorded in Japan or Ho (2011) for species recorded in Taiwan. Although Pythium spp.…”
Section: Morphologymentioning
confidence: 99%